PENINGKATAN PENGETAHUAN TENTANG PAPSMEAR SEBAGAI UPAYA DETEKSI DINI KANKER SERVIKS DI DUSUN BIRING ROMANG - Lili Purnama Sari; Sri Wahyuni Bahrum (Jurnal Abdi Insani, 2022)
The incidence of cervical cancer (cervical cancer) in Indonesia is the second highest in the world. Cervical cancer often does not cause symptoms and is difficult to detect at an early stage and is generally only detected when the stage is advanced. Information about cervical cancer is still not accessible to most women of childbearing age (WUS) in Indonesia. This community service activity aims to provide knowledge to mothers about the importance of having a Pap smear and the dangers of cervical cancer. The implementation method of this activity is measurement with a pre-post one group test design using a questionnaire as a measuring tool to determine mother's knowledge. The first measurement is before education and the second measurement is after education about the importance of Pap Smear examination as an early detection of cervical cancer. From the results of the pre test analysis as many as 65% of women of suburban age who became respondents did not know about the importance of having a Pap smear as an effort to detect cervical cancer early and after counseling the results of the Post Test showed as many as 89% of women of childbearing age understood the importance of having an examination. Pap smear as an effort to detect cervical cancer early. All participants were very enthusiastic in listening to the information conveyed, some of the participants stated that the activities would be beneficial, especially increasing knowledge and self-confidence as a woman to maintain women's health. The counseling participants, namely all women of childbearing age, can understand the importance of Pap Smear examination as an Effort for Early Detection of Cervical Cancer. People hope that there will be a free Pap smear that will allow them to know the condition of their cervix.